Sex differences in mapping and rhythm outcomes of a repeat atrial fibrillation ablation. (24th May 2021) - Pak, HN; Park, JW; Yang, SY; Kim, M; Yu, HT; Kim, TH; Uhm, JS; Joung, BY; Lee, MH
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The risk of procedure-related complications and rhythm outcomes differ between men and women after atrial fibrillation catheter ablation (AFCA). We evaluated whether consistent sex differences existed in mapping and rhythm outcomes in repeat ablation procedures. Methods: Among 3, 282 patients in the registry, we analysed 443 consecutive patients (24.6% female, 58.5 ± 10.3 years old, 61.5% paroxysmal AF) who underwent a second AFCA. We compared the clinical factors, mapping, left atrial (LA) pressure, complications, and long-term clinical recurrences after propensity score matching. Results: The LA volume index (43.1 ± 18.6 vs. 35.8 ± 11.6 ml/m2, p < 0.001) was higher, but LA dimension (40.0 ± 6.8 vs. 41.6 ± 6.3mm, p = 0.018), LA voltage (0.94 ± 0.55 vs. 1.20 ± 0.68 mV, p = 0.002), and pericardial fat volume (89.5 ± 43.1 vs. 122.1 ± 53.9 cm3, p < 0.001) lower in women with a repeat ablation than in their male counterparts. The pulmonary vein (PV) reconnections were lower (58.7% vs. 74.9%, p = 0.001), but the proportion of extra-PV triggers (27.5% vs. 17.0%, p = 0.026) and elevated LA pulse pressures (79.7% vs. 63.7%, p = 0.019) was significantly higher in women than men. There was no significant sex difference in the procedure-related complication rate (4.6% vs. 4.2%, p = 0.791). During a 31(8∼60) month median follow-up, clinical recurrences were significantly higher in women after both the de novo procedure (log rank p = 0.039, antiarrhythmic drug [AAD]-free log rank p < 0.001) and second procedure (log rank p = 0.006, AAD-free log rank p = 0.093). A female sex (HR 1.51 [1.06-2.15], p = 0.023), non-paroxysmal AF (HR 1.78 [1.30-2.34], p < 0.010), and extra-PV triggers (HR 1.88 [1.28-2.75], p = 0.001) were independently associated with clinical recurrences after repeat procedures. Conclusions: During the repeat AFCA procedures, PV reconnections were lower in women than men, and the existence of extra-PV triggers and an LA pressure elevation was more significant, which resulted in poor rhythm outcomes.